PENERAPAN MODEL PEMBELAJARAN PEER LESSONS DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AGAMA DI KELAS X SMK NEGERI 1 TELUKDALAM - Duha, Marlian (Unversitas Katolik Santo Thomas, 2022)
This classroom action research aims to determine the improvement of student learning outcomes in Protestant Christian religious subjects, by applying the Peer Lessons learning model in class X SMK Negeri 1 Telukdalam. The form of this research is Classroom Action Research (CAR), the learning process is carried out in two cycles and each cycle consists of four stages, namely: (1). Planning Phase; (2). Action stage; (3). observation stage; (4). Reflection stage. The research subjects were students of class X SMK Negeri 1 Telukdalam. The results of processing tests on student activities in the first cycle of the first meeting were obtained (62.50%) and at the second meeting (63.54%). while in the second cycle the first meeting was obtained (86.98%) and the second meeting was obtained (90.36%). and learning outcomes have increased